2019
DOI: 10.1002/oby.22561
|View full text |Cite
|
Sign up to set email alerts
|

β3‐Adrenergic Activation Improves Maternal and Offspring Perinatal Outcomes in Diet‐Induced Prepregnancy Obesity in Mice

Abstract: Objective Prepregnancy obesity is an epidemic disorder that seriously threatens both maternal and offspring health. This study investigated the effects of β3‐adrenergic receptor (β3‐AR) activation on the perinatal outcomes in a diet‐induced prepregnancy obese (PPO) murine model. Methods Four‐week‐old female C57BL/6 mice were fed high‐fat diet or chow diet for 16 weeks to yield PPO mice and chow‐fed (CF) lean mice, respectively. After successful mating with CF males, the PPO and CF mice were both randomly divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Therefore, if mitochondrial biogenesis got increased while mitophagy could be inhibited, it would be an ideal strategy for increasing beige adipocyte to promote energy consumption and treat obesity (16)(17)(18). Recent researches have shown that the β3-AR and its downstream PKA could drive the 'browning' effect in WAT, and some studies demonstrated that the activation of PKA would lead to promote mitochondrial biogenesis or inhibit mitophagy (19,20).…”
mentioning
confidence: 99%
“…Therefore, if mitochondrial biogenesis got increased while mitophagy could be inhibited, it would be an ideal strategy for increasing beige adipocyte to promote energy consumption and treat obesity (16)(17)(18). Recent researches have shown that the β3-AR and its downstream PKA could drive the 'browning' effect in WAT, and some studies demonstrated that the activation of PKA would lead to promote mitochondrial biogenesis or inhibit mitophagy (19,20).…”
mentioning
confidence: 99%